Sense of coherence and remedial behaviours of the young - Płaczkiewicz, Beata; Tucholska, Stanisława (Studia Psychologica: Theoria et praxis, 2009)
The researches reported in this paper seek the relationship between sense of coherence and coping styles. The studies embraced a group of 192 high-school adolescents (132 girls and 60 boys) aged between 17 and 18 years. Two methods have been used in this research: Antonovsky’s The Sense of Coherence Questionnaire (SOC-29) and Coping Inventory for Stressful Situations (CISS) authored by Endler and Parker. In addition cluster analysis carried on the results in scales and subscales of CISS Questionnaire resulted into three group of pupils. The groups were compared in respect of sense of coherence. An analysis of the obtained results showed a clear correlation between coping and the sense of coherence in all population of researched adolescents. There is a positive interrelation between Task-oriented coping and global sense of coherence and its components- the sense of comprehensibility, manageability and meaningfulness. Moreover, there were found significant correlations of SOC and its components with Emotion- oriented coping, but this time they appeared negative. Furthermore, there isnt relation between SOC and Avoidance- oriented coping associated with bewaring of thinking and experiencing stressful situations. What is interesting Distraction and Social Diversion which are subscales of Avoidance-oriented coping, correlate with SOC.